2011
DOI: 10.1037/a0025787
|View full text |Cite
|
Sign up to set email alerts
|

Psychological capital as a moderator between emotional labor, burnout, and job satisfaction among school teachers in China.

Abstract: In this study, we examined the relationship between emotional labor and burnout as well as job satisfaction. Besides, we also explored whether psychological capital (PsyCap) moderated the emotional labor-burnout or job satisfaction associations. In total, 264 full-time Chinese school teachers in China were recruited. Results showed that PsyCap was related to emotional labor, burnout, and job satisfaction in the hypothesized direction. Furthermore, PsyCap moderated the association between emotional labor and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
205
4
33

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(268 citation statements)
references
References 54 publications
26
205
4
33
Order By: Relevance
“…Recent research has also focused on teachers as "emotional laborers" [2,[9][10][11]. It has been stressed that emotional involvement is an integral part of the teaching profession [1,[12][13][14][15][16]. A significant majority of the teaching workforce is represented by women, which clearly corresponds with the fact that emotional labor is typical of those professions which are feminized [3,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has also focused on teachers as "emotional laborers" [2,[9][10][11]. It has been stressed that emotional involvement is an integral part of the teaching profession [1,[12][13][14][15][16]. A significant majority of the teaching workforce is represented by women, which clearly corresponds with the fact that emotional labor is typical of those professions which are feminized [3,17].…”
Section: Introductionmentioning
confidence: 99%
“…In practice, it may mean showing enthusiasm while conducting classes, reacting with empathy to pupils' worries and needs, hiding fatigue and annoyance or displaying positive emotions even when pupils are being difficult and rude. Teachers have to educate and, at the same time, manage their own emotions to meet the expectations associated with their profession [1,2]. In other words, they perform emotional labor.…”
Section: Introductionmentioning
confidence: 99%
“…According to the conservation resource model (Hobfoll, 2001) psychological capital, which is the personal resource of an employee, can moderate the association between peer relationship and their organizational commitment. Cheung, Tang and Tang (2011) further investigated the role of psychological capital as a moderating variable to explain the relationship between organizational commitment and peer relationship. …”
Section: Psychological Capital As a Moderatormentioning
confidence: 99%
“…Several studies have shown positive and negative connections between psychological capital and different work and organisational variables such as job satisfaction (Badran & Youssef-Morgan, 2015;Karatepe & Karadas, 2015;, organisational commitment (Larson & Luthans, 2006), engagement (Avey, Hughes, Norman & Luthans, 2008), efficacy , intention to leave the organisation (Avey, Luthans & Jensen, 2009;Schulz, Luthans & Messersmith, 2014), burnout (Cheung, Tang & Tang, 2011;Dinget al, 2015), and health and welfare in workers (Avey, Wernsing & Mhatre, 2011;Krasikova, Lester & Harms, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The PCQ has been the subject of validation studies in different countries, and it has generally been shown to have good psychometric properties (Cheung et al, 2011;ClappSmith, Vogelgesang & Avey, 2009;Görgens-Ekermans & Herbert, 2013;Luthans et al, 2005;Nigah, Davis & Hurrell, 2012;Rego, Sousa, Marques & Pinha, 2012;Wang, Liu, Wang & Wang, 2012). Azanza, Domínguez, Moriano and Molero (2014) wrote the Spanish adaptation of the PCQ, validating it in a sample of 372 workers.…”
Section: Introductionmentioning
confidence: 99%